Pengaruh Budaya Organisasi terhadap Motivasi Kerja, Komitmen, dan Kinerja Karyawan di SMAN 9 Pontianak - Liliyana -; Utin Nina Hermina; Desvira Zain (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study is aimed to describe and to find the influence of organization culture toward work motivation, commitment and performance. This study is conducted on Pontianak State Senior High School 9 in 2009. It is used permanent lecture as the sample of study they are 30 persons. Used variable consists of organization culture variable, lecture work motivation, lecture commitment and lecture performance. By using path analysis technique; it is known that commonly organization culture in Pontianak State Senior High School 9 is better. It is shown by the existence of significance influence toward work motivation, commitment and performance of lecture. Motivation is the most important factor that has biggest influence toward lecture performance. Thus, the principal of institution is expected to focus his attention toward motivation role. Beside, there should be any effort in increasing commitment by realizing that institution has strong supporting factor to increase this commitment. That is by lecture status as State Civil Officer.Keywords: Organization Culture, Work Motivation, Commitment, Lecture Performance